Exchange Rate Volatility, Financial Constraints, and Trade : Empirical Evidence from Chinese Firms - Heericourt, Jerome; Poncet, Sandra (World Bank, Washington, DC, 2014)
This paper studies how firm-level export performance is affected by Real Exchange Rate (RER) volatility and investigates whether this effect depends on existing financial constraints. The empirical analysis relies on export data for more than 100,000 Chinese exporters over the 2000-6 period. The results confirm a trade-deterring effect of RER volatility. Firms' decision to begin exporting and the exported value decrease for destinations with higher exchange rate volatility; besides, this effect is magnified for financially vulnerable firms. As expected, financial development seems to dampen this negative impact, especially on the intensive margin of export. These results provide micro-founded evidence suggesting that the existence of well-developed financial markets allows firms to hedge exchange rate risk. The results also support a key role of financial constraints in determining the macro impact of RER volatility on real outcomes.